Business Plan - Happy Fit - Cure, Thibault (2016)
The current business plan inspects Happy Fit, an all-in-one Park integrating a Trampoline Park, A Gym and a Child Care Centre in the same complex. The project aims at building a place where “All the people are Healthy and Happy together”. It emerged from the combined ideas and experiences of me, Thibault Cure, and Marc Oper, my father. We are a complementary team that fit this project thanks to our different educational backgrounds and work experiences. He will bring the credibility, the experience, the network and its portfolio of customers, while I will use my different work experiences and business management skills to run the business, and my creativity and youth to continuously innovate. We are proposing a range of more than 25 activities categorised in 3 business units: The Trampoline Park, the Gym and the Child Care Centre. In the first one, we will propose a broad array of programs like Open Jump Sessions, Dodgeball, Fitness and Specific Classes for everyone, events and parties. Concerning the Gym, we will support our clients through professional advisory, support and accompaniment. Moreover, collective and individual classes will be offered, as well as seminars where external speakers will share their knowledge on particular topics. During holidays, we will provide summer camps and teenagers parties. We will also offer additional services for groups, such as corporate events, birthdays and other special occasions. The Child Care Centre will propose temporary Child Care Services and Holiday camps, with low rates for members of the two other units. Finally, we will display a healthy food and drink refreshment area, and a shop for merchandised products and sports related goods, that will contribute to create a community feeling and to build brand identity. We want to change the way people exercise, and allow them to mix amusement and healthier lifestyle. The concept is simple. Around the Trampoline Park, we will build a complex that creates a favourable environment for people to exercise, have fun and engage with others. Every business unit will support each other, and all of them will work in parallel. We want to create a feeling of community between people from totally different social classes, thanks to the diversity and complementarity of our activities. Indeed, we will provide a range of activities that can fit anyone: families, children, seniors, experienced sportsmen and people in situation of handicap or obesity. We want to capitalise on the current diversity of cultures, social classes, capacities and ages that characterize New Caledonia, and use it as a strength. We will first implement the Trampoline Park (Main Unit of the business) and the Gym, and implement the set of activities progressively. On the 3rd year, the Child Care Centre will be launched accordingly with the demand and affluence, which will come as a support of the others, and add more convenience for families to our concept. We will grow progressively, to make sure we will meet customers’ expectations in terms of safety and quality. Finally, we will try to keep our prices as low as possible in order to allow families from every income to afford it. We are already in discussion with two local town-halls and the main disabled societies in New Caledonia, who are interested in the project as it goes along with their social commitment. The Market will be located in New Caledonia (269,000 people) and more precisely in the Grand Nouméa area, which represents 2/3 of the total population. The diversity of activities will allow us to generate revenues at any period of the year, and the uniqueness of the concept as well as its “all-in-one” aspect represent our main competitive advantage towards our competition, which remains limited to the Fitness and Health industry, as there is no such infrastructure for the leisure and entertainment one. The investment necessary for the realization of such a complex is 309,7 million XPF. 65% of this amount will be used to build the facility, which represents a safe investment in property. This investment is capital-intensive. 30% of this amount will be dedicated to the purchase of the equipment for the Park, and 4% for the initial treasury. We expect our business angel to invest for 93% of the total capital required, the 6% left will come from our personal contribution and from local subsidies. This investment, in addition to its profit aspect, must be seen as a social investment in local communities, as part as a foundation. The business is expected to become profitable after only 11 months and to generate 18 million XPF profit after 3 years.